How to Communicate Value Added Care: Negotiation and Saying No - Pamela Duke; Nan Cochran (Association of American Medical Colleges, 2014)
Abstract Introduction Educators have recently been challenged to actively incorporate instruction that emphasizes value-added care into the curriculum in a meaningful manner. This workshop defines value-added care, its importance for the practice of medicine, and communication strategies to enhance discussions with patients. Methods Within this workshop evidence-based communication strategies are clearly outlined that aid in sharing information and in successful negotiation with patients over unnecessary tests and treatments. The workshop is interactive with roleplays and self-reflection exercise. This workshop is suitable for medical students, residents, physician assistants, advanced nursing students or practicing physicians and can be adapted from its 2-hour format into two 1-hour sessions. The attachments include: a detailed facilitator guide, PowerPoint with annotations, role play with feedback form, pre- and postsession surveys, and a reference list. Results This workshop was given to practicing physicians and residents in various specialties including family practice, internal medicine, obstetrics and gynecology, geriatrics, and palliative care. Feedback from the workshop showed that attendees thought the program was effective and would recommend it to colleagues (87% agreed or strongly agreed). Eighty-seven percent of participants planned to change their behavior as a result of the training (agreed or strongly agreed). In providing open-ended feedback, participants mentioned that the audience felt very engaged and interested in the topic of value added care and was eager to learn practical skills for implementing in their practice: "I really enjoyed learning about the topic and the idea of talking with the patient about cost." Participants cited the role-plays as useful: "I enjoyed the ability to practice as the most useful part of the workshop." Instructive feedback from the sessions taught us that we need to provide time for discussion about the topic, and that "a little more time to practice would be useful." In addition, we learned that it was important to allow enough time in the workshop for role-plays, debriefing after the role-plays, and for learners to discuss their take-home skills: "I would have liked more time to ask questions [about] the material and debrief the role-play." Discussion In the future, we would like to evaluate a larger amount of data from a variety of small group workshops and to discriminate by type of learner.